Forecasting the Rupiah Exchange Rate Influenced by Several Factors Using the Improve Grey Model (1,3) - Pratiwi, Dian Meilin; Firdaniza, Firdaniza; Kusuma, Dianne Amor (Jambura Journal of Mathematics, 2025)
The rupiah exchange rate is one of the important indicators of a country's economic stability, but the rupiah exchange rate often fluctuates following the factors that influence it. Forecasting the rupiah exchange rate is very important for economic planning, it helps the government make monetary policy decisions to maintain the stability of the rupiah exchange rate. Common methods used to forecast the rupiah exchange rate are ARIMA, FTS Markov Chain, and exponential smoothing. These methods are widely used to show the relationship between variables, but these methods have the disadvantage that they must meet the assumptions of data patterns. The contribution of this research is the use of the improve Grey model (1,3) predict the rupiah exchange rate in 2024, which is influenced by inflation and the balance of payments. The improve Grey model (1,3) was chosen because it does not require data distribution assumptions and can consider several external factors, thus providing more specific results for certain fields. The improve Grey model (1,3) uses the Grey model (1,1) to calculate the parameter values of the independent variables in the calculation of the improve Grey model (1,3) whitening equation. The calculation of the improve Grey model (1,3) whitening equation is calculated using a first-order ordinary differential equation. The use of the improve Grey (1,3) model for forecasting the rupiah exchange rate is considered accurate based on the Mean Absolute Percentage Error (MAPE) value. The rupiah exchange rate influenced by inflation and the balance of payments using the improve Grey model (1,3) for 2024 is predicted to increase from the previous year to Rp. 18.076, which indicates a weakening in value. This weakening has a positive impact on the balance of payments and a negative impact on inflation.